Сomparative analysis of wind correlation lidar sounding range in UV, visible band and near IR bands - S. E. Ivanov (Nauka i Obrazovanie, 2014)
The paper presents a comparative analysis of the sounding range of wind correlation lidar in ultraviolet, visible, and near infrared spectral bands. It shows that a visible spectral band is the most advanced one to provide a maximum sounding range of wind correlation lidar in earth atmosphere. If there are specific requirements for wind correlation lidar, for example, a requirement is that a wind correlation lidar should operate at the eye-safe laser sounding wavelength then the efficient work of wind correlation lidar may be maintained in ultraviolet and near infrared spectral bands with the sounding range reduced a little bit.